Developing and validating a computerized oral proficiency test of English as a foreign language (Coptefl) - Isler, Cemre; Aydin, Belgin (Ijate-Int Journal Assessment Tools Education, 2021)
This study is about the development and validation process of the Computerized Oral Proficiency Test of English as a Foreign Language (COPTEFL). The test aims at assessing the speaking proficiency levels of students in Anadolu University School of Foreign Languages (AUSFL). For this purpose, three monologic tasks were developed based on the Global Scale of English (GSE, 2015) level descriptors. After the development of the tasks, it was aimed to develop the COPTEFL system and then compare the test scores and test-takers' perspectives on monologic tasks between the COPTEFL and the face-to-face speaking test. The findings from these quantitative and qualitative analyses provided substantial support for the validity and reliability of the COPTEFL and inform the further refinement of the test tasks.
Keywords: Language testing; Oral proficiency testing; Computerized oral proficiency testing; English language learners; EFL context